ChatGPT, a Product of AI, and its Influences in the Business World - Arman, Md.; Lamiya, Umama Rashid (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2023)
Specifically the study analyzes how ChatGPT AI is transforming business operations and enhancing customer experience in customer service, e-commerce, healthcare, finance, marketing, and developer business sectors. Using a comprehensive literature review approach.The study explores the implications of ChatGPT AI for businesses, including its potential to improve efficiency, reduce costs, and enhance competitiveness. Additionally, ethical and legal considerations surrounding the use of ChatGPT AI in business operations are evaluated, including issues related to data privacy, bias, and transparency.The study provides insights into future directions for the application of ChatGPT AI in business and the potential impact of this technology on various business sectors. The objective is to provide a comprehensive review of the influence of ChatGPT AI on businesses, its potential benefits, and challenges for businesses looking to adopt this technology. Overall, this study highlights the importance of considering the benefits and limitations of AI adoption in businesses, as well as the ethical and legal implications of its use.